(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2008)
Researches on verbal correspondence can help identifying variables that intervene in treatment adherence, since it is verified the relation between what the patient says and what he/she does. This study had the purpose to describe and analyze the correspondence say-do, in its natural occurrence, of three female adults, with type 2 diabetes mellitus, about their practice of physical exercises. It was asked to the participants if they would practice physical exercises. Later, this practice was filmed. The data show that one participant showed good correspondence, another one showed partial correspondence and the third one did not present any correspondence. Analyzing the demographic data of the participants, it was hypothesized that some variables, such as schooling, social-economic level, age and sedentariness may be related to the level of verbal correspondence.